Enzymatic hydrolysis as an approach to produce alternative protein from cephalopods ink powder: A short review - Ayu Shazwani, Z.; Rabeta, M.S. (Rynnye Lyan Resources, Malaysia, 2020)
Cephalopoda is a class of Mollusca that lives in marine environments, well-known as the most distinctive features of their ink especially squid and cuttlefish species. The various valuable constituents in their ink have been used over millennia for practical and commercial purposes. The current world population of 7.6 billion is expected to reach 8.6 billion in 2030, 9.8 billion in 2050, and 11.2 billion in 2100. Thus, the amount of food, types of food in demand, and their relative contribution to diets will all change.